2014
DOI: 10.1002/pon.3577
|View full text |Cite
|
Sign up to set email alerts
|

Identification of posttraumatic growth trajectories in the first year after breast cancer surgery

Abstract: This study was the first longitudinal examination of PTG trajectories and their different levels of adjustment. The findings support our argument that identifying distinct PTG trajectories can better determine the nature of the relationship between PTG and adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
4
41
1
Order By: Relevance
“…1316, 19 However, these results contradict previous findings from longer-term research, in which PTG rose steadily during the 1.5–2 years following breast cancer diagnosis. 17 In our earlier analysis of this dataset using random effects models, we found an approximate 10-unit increase in PTGI over time.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…1316, 19 However, these results contradict previous findings from longer-term research, in which PTG rose steadily during the 1.5–2 years following breast cancer diagnosis. 17 In our earlier analysis of this dataset using random effects models, we found an approximate 10-unit increase in PTGI over time.…”
Section: Discussioncontrasting
confidence: 80%
“…1, 18, 19, 21 This study identified trajectories of PTG during and after cancer treatment in a large longitudinal dataset of women with breast cancer. The best-fitting model yielded six trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the relationship between perceived growth and anxiety and depression in cancer patients and survivors is mixed. Whereas some studies indicate that perceived growth and depression and anxiety are not related (Cordova et al, 2001; Salsman, Segerstrom, Brechting, Carlson, & Andrykowski, 2009; Shand, Cowlishaw, Brooker, Burney, & Ricciardelli, 2015), others suggest that perceived growth may be associated with lower levels of depression (Leong Abdullah et al, 2015; Shand et al, 2015; Wang, Chang, Chen, Chen, & Hsu, 2014) and higher levels of anxiety (Leong Abdullah et al, 2015). However, the magnitude of these relationships is generally weak.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with breast cancer live with an awareness of the "disease" for a long time because there is a risk of recurrence and metastasis of the cancer for ten years after surgery, the common initial treatment. For this reason, it has been anticipated that they will suffer from pain of various kinds and many studies have addressed physical and mental pain after surgery for breast cancer [2] [3] [4]. Further, Taylor [5] and Wand [6] have addressed the benefit finding (BF) that improves the will to live of patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%